Fiscal Incentive Effects of the German Equalization System - Stehn, Sven Jari (IMF Working Papers; Working Paper ;, 2009)
Does reliance on transfers weaken fiscal discipline and encourage pro-cyclical fiscal policies in recipient subnational governments? Using fiscal reaction functions for a panel of the German Lander, this paper finds a positive answer to both questions. Net-recipient states (Lander, benefiting from the transfer system) have not reduced primary expenditure significantly in response to rising deficits, but have instead relied on vertical transfers from the federal government to ensure debt sustainability. Moreover, they have pursued pro-cyclical policies, particularly by raising expenditures in good times. Net-contributing Lander (paying into the transfer system), in contrast, have ensured fiscal sustainability through spending adjustments; they have also been less pro-cyclical. Panel vector auto-regressions confirm these findings.